Goal orientation and mastery climate: a review of contemporary research and insights to intervention - Valentini,Nadia Cristina (2006)
This manuscript is a review of human achievement motivational theory, that emphases goal orientation and mastery climates. Specifically, it provides an overview of goal orientation researches and discusses how much the implementation of motivational climates in learning settings affects children and adolescents' psychological and behavioral responses. The manuscript concludes with further discussion about researches in this field, and emphases the in learning environments practical application.